Ergonomics the practical approach - Safetycare Australia Pty. Ltd. (Australia : Safetycare Australia Pty Ltd. (production) ; Kuala Lumpur : Safetymax Sdn. Bhd. (dictridutor), 1993)
This video discusses the practical approach of ergonomics and relationship between people and equipment they use and the physical environment in which they work
Title from title screen
Keywords: Human engineering -- Safety measure; Human engineering; Industrial safety